Analytical solution to a hydrodynamic model in an open uniform reservoir - Kaboon Thongtha; Jaipong Kasemsuwan (My University, 2017)
The hydrodynamic model is used to determine the water wave flow. In this research, a nondimensional form of a two-dimensional hydrodynamic model with generalized boundary condition $g(x,t)$ and initial conditions for describing the elevation of water wave in an open uniform reservoir is proposed. The separation of variables method with mathematical induction is employed to find an analytical solution to the model. An example of flow calculations in an open uniform reservoir is also demonstrated.
Keywords: Potential flow; Aquatic and Environmental Studies